Pengaruh Customer Online Reviews, Flash Sale dan Tagline Gratis Ongkir terhadap Pembelian Impulsif pada Aplikasi Tik Tok - Ali Zaki Nur Romadhoni; Dian Ayu Liana Dewi (Komunitas Dosen Indonesia, 2025)
Impulsive buying is an act of purchasing done suddenly without any consideration, which can lead to regret. The aim of this study is to demonstrate how flash deals, customer online reviews, and the phrase